Popular sovereignty in early modern constitutional thought - Lee, Daniel, 1979- (Oxford : Oxford University Press, 2016)
Examining the intellectual origins of the constitutional doctrine of 'popular sovereignty', this volume explores the importance of Roman law as a chief source of modern constitutional thought.
Includes bibliographical references and index.
Specialized.
Description based on online resource; title from home page (viewed on March 9, 2016).
Keywords: Sovereignty -- History; Roman law -- Influence; Politics and Government; Politics & government